Blended Student Learning Experience: Combining Virtual Learning Environment, 3D Design and Active Community Engagement within a Framework of Knowledge Transfer Program - Yusvana, Rama; Roslinazairimah, Zakaria; Farahanim, Misni (2015)
In this era of digital information, teaching tools and learning resources have now become more widely available and accessible to both students and academics to use. This opens a possibility to create a blended and more engaging / stimulating learning experience for students to increase their understanding of a particular topics or concept given during the class. Some of the tools to achieve this objective are the use of free and easy to use ‘3D design’ to improve students spatial abilities - particularly for engineering and science students, as well as internet-based Virtual Learning Environment (VLE) that students can use at their own pace. In addition, hands-on experience and an opportunity to verbally communicate the knowledge learned in the class to other people, such as the local community, would enhance student understanding and learning experience.